Analysis of Restorative Justice in Gender-Based Violence Cases Within Diversion Under Law No. 12 of 2012 - Romadlany, Zakiah (Universitas Islam Negeri Sumatera Utara, 2024)
The handling of cases involving gender-based violence against children in conflict with the law in Indonesia often remains trapped in a conventional criminal law approach that does not consider the special needs of children. This article analyzes the application of restorative justice principles in the context of diversion according to Law No. 12 of 2012 on the Juvenile Justice System. This research employs a normative approach, examining sources from various literatures, including books, laws, and other relevant literature related to the theme of this writing using the restorative justice framework. The findings of this study indicate that the restorative justice approach focuses on restoring relationships among the perpetrator, victim, and society, while promoting social responsibility. By adopting the principles of The Beijing Rules, this new law provides space for more humane and rehabilitative case resolutions. Through in-depth analysis, it is found that effective implementation of diversion can prevent negative stigma and assist in the reintegration process of children into society. The results of this study are expected to contribute to the development of policies that are more responsive to the rights and needs of children in the context of gender-based violence.